PERBANDINGAN KERAGAAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) PADA SISTEM PEREMAJAAN KONVENSIONAL DAN UNDERPLANTING - Ayu Nurjanah; Aries Sukariawan; Dina Arfianti Saragih (Agro Estate, 2021)
Rejuvenation is the replacement of new unproductive plant with new plants that are more productive and profitable. In the cultivation of oil palm there are several alternative models of rejuvenation that can be applied including conventional rejuvenation, underplanting rejuvenation and conventional rejuvenation with intercropping. This research was conducted in the Rambutan PTP. Nusantara III (Company). The time of the study was carried out in February to July 2019. This research was conducted using descriptive analysis method, namely by collecting primary data and secondary data. Primary data, each data for conventional rejuvenation and underplanting model that is. Morfological observation (midrib) and secondary data. Each data for conventional rejuvenation and underplanting model viz, insert (2017, 2018, 2019) and interest and Fruit Calculation Data. The results showed that conventional rejuvenation techniques at the time before planting carried out include several stages including the felling of old plants and tillage until the area was ready for replanting so as to reduce the level of pest infestation and provide ideal soil for plant growth in the field. Mean wile for underplanting planting system places the insertion height ths hetat occurs in underplanting planting system which replace the disruption of young plant growth after the undisciplined implementation of underplanting technique. Poisoning of old plants is late and results in late mutation from TBM to TM ieless interest and fruit in the underplanting technique.